The Crackdown on Rights-advocacy NGOs in Xi's China: Politicizing the Law and Legalizing the Repression. Issue 136 (4th July 2022) - Zhu, Han; Jun, Lu
ABSTRACT: This article is the first to systematically study and compare the criminal repression of civic NGOs under the rule of Hu Jintao and Xi Jinping. The crackdown is analyzed against the evolution of NGO governance strategy that has bifurcated into co-option and repression. Under Xi's administration, the mode of repression has escalated from hooligan-style intimidation to law-based systematic crackdown, facilitated by an increasingly authoritarian legality. Underlying this escalation is the paradigm shift of governance strategy from 'maintaining stability' to 'consolidating state security.' Consequently, NGOs with evident pro-liberal inclination, mass mobilization capacities, and/or closer associations with 'hostile forces' are most vulnerable to persecution. This article concludes by gauging the impact of the crackdown on advocacy NGOs and suggesting possible scenarios for future rights activism.